The Effect of Product Quality to Purchase Decision at Safary Milk D’Kandang Amazing Farm Depok - Maidar Simanihuruk (Program Studi Hospitality dan Pariwisata, 2021)
To achieve the desired product quality, a quality standardization of the product is needed. This method is intended to ensure that the products produced meet the predetermined standards so that consumers will not lose confidence in the product concerned. Consumers will make a purchase decision if the product is considered to have high quality. The quality of the product will be felt after the item is consumed or used so that consumers will feel satisfied with the product purchased. The purpose of this study is to determine the impact of product quality on purchase decision at the Safary Milk D’Kandang Amazing Farm Depok. The Method of research used is quantitative methods in order to obtain more comprehensive, valid, reliable, and objective data. The sample consists of 100 visitors who visited the Safary Milk D’Kandang Amazing Farm Depok, selected based on the Probability Sampling with Simple Random Sampling technique. The factor and simple linear regression analysis were used for the data analysis with SPSS 22.0. The results of the study showed that product quality has a positive influence significantly contributed to the purchase decision at the Safary Milk D’Kandang Amazing Farm Depok (t = 11.955 > t table with a significance of 0.000 (ρ < 0.05) and that is proved by the score of R = 0.770. From the coefficient of determination, it can be concluded that the Purchase Decision is influenced by the Product Quality variable by 59.3% and the remaining 40.7% which is influenced by other variables.Keywords: Product Quality, Purchase Decision